TENDENCY RASPROSTRANENIYA NATIONAL VALUES AMONG THE YOUTH (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article discusses modern trends in promoting national values among young people. National values are the cultural heritage, historical identity and spiritual foundations of each nation. Family, educational institutions, mass media and social networks play an important role in shaping the national consciousness of the new generation. We can offer modern technologies, cultural events and educational programs as effective methods of promoting national values. The article also analyzes the impact of globalization on national identity and the attitude of young people to spiritual values. In the modern era of globalization, the issue of preserving national identity and cultural heritage of young people is becoming especially important. National values are a set of fundamental elements reflecting the cultural, historical and spiritual characteristics of each nation. They ensure the unity, identity and stability of the nation. The trend of promoting national values among young people is realized through education, cultural events, digital technologies and social movements.
Keywords: National values, youth, identity, culture, globalization, traditional heritage, education, social networks.